2010
DOI: 10.1097/yct.0b013e3181c189f7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pharmacotherapy With Electroconvulsive Therapy in Prevention of Depressive Relapse

Abstract: Comparative efficacy of c-pharm early and late strategies in providing improved protection against post-ECT relapse of major depressive disorder needs to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Another approach would be to start study medication prior to ECT, thereby maybe reducing the risk of early relapse and making the design more acceptable for patients and clinicians. This is supported by the study by Yildiz et al [23] who found a significant reduction in relapse when trial medication was started early compared to later in the ECT course but not by the study by Prudic et al [24], who found no difference in relapse rates when pharmacotherapy was started before or after ECT. However, if patients are randomised before remission has been obtained, the outcome of the post-randomisation acute treatment needs to be taken into account.…”
supporting
confidence: 75%
“…Another approach would be to start study medication prior to ECT, thereby maybe reducing the risk of early relapse and making the design more acceptable for patients and clinicians. This is supported by the study by Yildiz et al [23] who found a significant reduction in relapse when trial medication was started early compared to later in the ECT course but not by the study by Prudic et al [24], who found no difference in relapse rates when pharmacotherapy was started before or after ECT. However, if patients are randomised before remission has been obtained, the outcome of the post-randomisation acute treatment needs to be taken into account.…”
supporting
confidence: 75%
“…Three RCTs (Lauritzen et al, 1996;Sackeim et al, 2001;Yildiz et al, 2010) provided extractable data at 3 months and seven (Imlah et al, 1965;Kay et al, 1970;Krog-Meyer et al, 1984;Lauritzen et al, 1996;Sackeim et al, 2001;Seager and Bird, 1962;van den Broek et al, 2006) at 6 months. Relapse rates were 62.7% (95% CI ¼ 47.6-75.8%, I 2 ¼ 0) at 3 months and 65.5% (95% CI ¼ 49.7-78.5%, I 2 ¼ 72%) at 6 months.…”
Section: Relapse Rates In Untreated Samplesmentioning
confidence: 99%
“…For the 3-month follow-up, three placebo-controlled RCTs (N ¼ 128) provided extractable data: two (Lauritzen et al, 1996;Yildiz et al, 2010) evaluating selective serotonin reuptake inhibitor (SSRI) monotherapy vs placebo and the other (Sackeim et al, 2001) comparing TCA monotherapy and TCA-lithium combination to placebo. The first Figure 3 Outcomes at 3, 12, and 24 months following ECT.…”
Section: Rr Of Relapse On Continuation Antidepressant Pharmacotherapymentioning
confidence: 99%
“…A double-blind, placebo, controlled trial found that early pharmacotherapy with sertraline provided protection against relapse, with a relapse rate of only 14% (Yildiz et al, 2010). Nortriptyline plus lithium has also been suggested as a useful combination therapy to prevent relapse following ECT (Sackeim et al, 2001), though ultimately the optimal therapy is likely to be determined at an individual level.…”
Section: Does Ect Prevent Relapse?mentioning
confidence: 99%